URGENSI PENGATURAN PRINSIP MINIMAL UTANG SEBAGAI SYARAT KEPAILIATAN BAGI DEBITOR - Revita Pirena Putri; Endang Prasetyawati (Gapenas Publisher, 2023)
Bankruptcy is an example of a form of effort that can be taken by the parties as an effort to ask for accountability. In Article 2 paragraph (1) of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Obligations for Payment of Debt, it regulates the requirements for a debtor to be declared bankrupt by the Court. There are at least 3 requirements, namely, the debtor has 2 or more creditors, there is at least one debt that has not been paid in full and there is debt that is due and collectible. However, in relation to these requirements, Indonesia has not regulated the provisions for the amount of debt borne by the debtor so that the debtor can be declared bankrupt. Problems will arise, if the debtor who is bankrupt is a debtor who has a greater amount of wealth compared to the debt he has. This study aims to find out, understand and explain the urgency of minimum debt arrangements as a condition for debtors to be bankrupt. The research method used is normative juridical with statutory law approach, approach and comparative approach through sources of primary legal materials, secondary legal materials and tertiary legal materials which are collected using collection techniques in the form of inventorying and categorizing legal materials which are then analyzed using prescriptive analysis techniques. The results of this study are that the minimum debt principal arrangement is a condition that must be regulated in bankruptcy arrangements in Indonesia. The existence of minimum debt requirements for filing for bankruptcy against debtors can provide legal protection for debtors